2015
DOI: 10.3109/08916934.2015.1022163
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of persistent Epstein–Barr virus (EBV) causes secretion of thyrotropin receptor antibodies (TRAbs) in EBV-infected B lymphocytes with TRAbs on their surface

Abstract: antibodies (TRAbs). We have reported that Graves' disease patients and healthy controls have EBV-infected lymphocytes that have TRAbs on their surface (TRAb(+)EBV(+) cells) in peripheral blood mononuclear cells (PBMCs). EBV reactivation is known to be associated with plasma cell differentiation and antibody production of B cells. In this study, we investigated whether TRAb(+)EBV(+) cells really produce TRAbs or not when persistent EBV is reactivated. We cultured PBMCs from 12 Graves' disease patients and 12 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 19 publications
1
32
1
Order By: Relevance
“…EBV reactivation and plasma cell differentiation occur in the same period (10,18,19). We examined Ig secretion during EBV reactivation induction and observed significant biphasic variations in IgG, IgM, and IgE with peaks on days 0 and 10 or 12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EBV reactivation and plasma cell differentiation occur in the same period (10,18,19). We examined Ig secretion during EBV reactivation induction and observed significant biphasic variations in IgG, IgM, and IgE with peaks on days 0 and 10 or 12 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs were cultured for 2 days in RPMI 1640/10% FBS with 0.1 μg/mL cyclosporin A at 37°C, as described in our previous study (18,19), to suppress T cell function and enrich the B cell population. They were then transferred to a culture at 33°C to induce EBV reactivation and were regarded as day 0 samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nagata has shown that in vitro reactivation of the EBV infection causes the production of thyrotropin receptor antibodies (TRAbs) in EBV-infected B-cells with TRAbs on their surface [48]. Moreover, Nagata has also reported increased TRAb titres in children with infectious mononucleosis due to EBV primary infection [23].…”
Section: Epstein-barr Virus As An Aetiological Factor In Autoimmune Tmentioning
confidence: 99%